Znormalizowane systemy zarządzania źródłem innowacyjności przedsiębiorstw - Ejdys, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Among mid-size companies especially popular are quality management, environmental management and occupational safety systems, all regarded as instruments of a systemic and complex approach to the problem of management-of selected areas. The implementation of formalized management systems has both advantages and disadvantages. This is confirmed by numerous research analysis in which participants often indicate both the advantages and barriers of having this kind of a system. The objective of the paper is to identify the means for continual improvement of formalized systems and their role in the process of innovation implementing. The author has made an attempt to define paths toward the intelligent organization built on the basis of formalized ISO management systems. This paper also explores the potential for linking quality, environmental and occupational and safely management systems with organizational and product innovation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 13-22